2013
DOI: 10.1007/s12070-013-0673-3
|View full text |Cite
|
Sign up to set email alerts
|

Tympanoplasty in Subtotal Perforation with Graft Supported by a Slice of Cartilage: A Study with Near 100 % Results

Abstract: The aim of this study is to evaluate the results of closure of subtotal perforation by tympanoplasty using underlay technique with the perichondrium/temporalis fascia graft supported by single cartilage slice anteriorly. Our hypothesis was that the cartilage support, single slice, offers an extremely reliable method for reconstruction of the tympanic membrane in cases of advanced middle ear pathology and Eustachian tube dysfunction. Retrospective and prospective study of patient undergoing tympanoplasty in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…It is an important prognostic factor for the success in tympanoplasty. 8 ET dysfunction secondary to infection and inflammation can be treated with medications, but the bony narrowing of pretympanic segment demands the surgical modification in middle ear keeping in mind the post operative hypoventilation of middle ear. Surgical modification can be done by using cartilage graft, for better stability and thus preventing medialisation of the graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important prognostic factor for the success in tympanoplasty. 8 ET dysfunction secondary to infection and inflammation can be treated with medications, but the bony narrowing of pretympanic segment demands the surgical modification in middle ear keeping in mind the post operative hypoventilation of middle ear. Surgical modification can be done by using cartilage graft, for better stability and thus preventing medialisation of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…This offers extremely reliable method for reconstruction of tympanic membrane in cases of ET dysfunction. 8 In cases of severe ET dysfunction due to pretympanic segment narrowing, balloon tuboplasty of the pretympanic segment can be combined with tympanoplasty, resulting in significantly high graft take up rate and restoration of middle ear integrity. 9 , 10 In our study, we found that decrease in pretympanic diameter and Reid plane-ET angle coexist with ET dysfunction, thus demanding intraoperative surgical modifications.…”
Section: Discussionmentioning
confidence: 99%
“…21 Mundra et al, achieved 98.94% of success in terms of graft uptake by using a slice of cartilage support in subtotal perforations, by underlay technique. 22…”
Section: Resultsmentioning
confidence: 99%
“…Mundra et al . found residual perforations in only 1.06% using perichondrium/temporalis fascia supported by cartilage . Although TM closure rates seem to be higher in grafting techniques using a combination of perichondrium or temporalis muscle fascia and cartilage, this procedure is time‐consuming and would not be necessary in the majority of patients.…”
Section: Discussionmentioning
confidence: 99%